PTSD in SJS/TEN: prevalence and risk factors. (26th April 2019) - Hefez, L.; Zaghbib, K.; Sbidian, E.; Valeyrie‐Allanore, L.; Allain, M.; Duong, T.A.; Colin, A.; Bellivier, F.; Romano, H.; de Prost, N.; Chazelas, K.; Chosidow, O.; et al.
Summary: Epidermal necrolysis is a rare and severe syndrome, mainly caused by a reaction to a medication, which causes severe blistering and sloughing of skin and mucous membranes. It includes two syndromes, Stevens‐Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN), depending on the percentage of body surface area involved. Incidence in France is one to two cases per million people. Multiple long‐term consequences of this violent and acute disorder are known about, mostly affecting skin and eyes, but also psychological distress, called post‐traumatic stress disorder (PTSD). However, commonness and risk factors of PTSD are still largely unknown. The present study was conducted by the research team of the national reference centre for toxic bullous diseases, based in Henri Mondor hospital, Créteil, France. We aimed to assess the prevalence and the risk factors of PTSD. We included 31 adult patients admitted at the acute phase (i.e. at its most severe) of SJS/TEN from 2009 to 2013. All of them were evaluated by a psychiatrist with several psychologic scores at the acute phase and were prescribed an anti‐anxiety drug, hydroxyzine, if necessary, then patients were checked again at two, six and 12 months. The degree of post‐traumatic stress was defined by a PTSD Checklist score of greater than 44. At six months, the PTSD prevalence was 23%. Three patients developed a late PTSD at 12 months. We conclude that a systematic psychiatric evaluation is warranted at the acute phase and must be followed by a prolonged and repeated evaluation of the patients for at least one year. Abstract : Linked Article:  Hefez et al. Br J Dermatol 2019; 180 :1206–1213